Komunikasi Antarpribadi Antara Anggota Keluarga dalam Mendukung Penderita Autoimun (ODAMUN) - Veronika Trimardhany (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2021)
ODAMUN stands for People with autoimmune patients. Autoimmune disease is a disease where the immune system that is formed incorrectly identifies foreign objects, where cells, tissues or organs of the human body are actually considered foreign objects so that they are damaged by antibodies. So the presence of autoimmune disease does not have an impact on increasing the body's resistance to a disease, but instead occurs damage to the body due to the formed immunity. Therefore, support from family members becomes very important for autoimmune sufferers. Communication in the family can also be interpreted as a readiness to talk openly about every problem in the family, both pleasant and sad, this is where members will be ready to solve the problems they face by talking to each other with patience, honesty and openness. Communication that occurs, among others, interpersonal communication between family members. The methodology in this study uses descriptive qualitative with a phenomenological approach by describing the experiences of four people with autoimmune disorders accompanied by their families. The results obtained are that they carry out interpersonal communication effectively with the following factors: openness, empathy, supportive attitude, positive attitude and equality. Of the five factors, the most prominent is the supportive attitude of the sufferer, this is what the sufferer always hopes to motivate to recover. Initial complaints from autoimmune sufferers are fever all over the body, canker sores, red rashes, but each sufferer has different complaints, but most of them are weak and powerless. The solution for sufferers is to go to the doctor, manage stress and always think positively in all situations, while family members provide support, namely accompanying when complaints come and immediately taking them to the hospital.